Peningkatan Motivasi Belajar Kimia Siswa Sekolah Menengah Menggunakan Metode Koligatif Kemas Kreatif (K3) - Suci Rizki Nurul Aeni (EduChemia)
Abstract: This research is classroom action research at XII class of Madrasah Aliyah YAPIKA. The subject matter  properties of Colligative Solution conducted with K3 method (Koligatif Kemas Kreatif) to improve student’s learning motivation. Research has been conducted with the repetition of three times so that the study be completed for three years. Three phase of learning are preparation, implementation and evaluation. Preparation phase is done by teachers and students at home. The teacher is preparing the learning media there are games rules, cardboard spacecraft, question cards,  stopwatch, and a dice. Students learn the material properties of koligatif independently learning by themself using  the student hand book. Implementation of the learning is done through a number of methods, there are the story method, discussions and cooperative teamwork through creative games. The evaluation was direct observation methods. The observation sheets assessing of cognitive and affective aspects of students. Based on the results of observation showed that students can impact the content, focus attention and participate active in learning, supported by innovations that have been implemented. Keywords: Colligative properties, K3, Motivation Abstrak: Penelitian ini adalah penelitian tindakan kelas di Madrasah Aliyah YAPIKA Kurnia kelas XII yang mengkaji materi Sifat Koligatif Larutan melalui metode pembelajaran K3 (Koligatif Kemas Kreatif), sebagai cara untuk meningkatkan motivasi belajar siswa. Penelitian telah dilakukan dengan pengulangan sebanyak tiga kali. Pembelajaran yang ditempuh berupa tahap persiapan, pelaksanaan dan evaluasi. Tahap persiapan dilakukan oleh guru dan siswa di rumah. Guru mempersiapkan media pembelajaran berupa petunjuk games, karton wahana, question card, stopwatch, dan dadu. Siswa mempelajari materi sifat koligatif secara mandiri dengan cara belajar melalui buku pegangan siswa. Pelaksanaan pembelajaran dilakukan melalui sejumlah metode yaitu metode kisah, diskusi dan games kreatif melalui kerjasama tim secara kooperatif. Evaluasi dilakukan melalui metode observasi langsung. Lembar observasi tersebut menilai aspek kognitif dan aspek afektif siswa. Berdasarkan hasil observasi menunjukan bahwa pada umumnya siswa dapat menguasai konten, memusatkan perhatian dan berpartisipasi aktif pada pembelajaran ditunjang oleh inovasi yang telah dilaksanakan. Kata Kunci: Sifat koligatif, K3, Motivasi